Analysis of Scientific Knowledge on The Process of Making Tempeh Gembus as Local Wisdom and Its Potential for Empowering Students' Analytical Thinking Skills - Fajri, Lulu Nur; Suciati*, Suciati; Fakhrudin, Isma Aziz; Silvita, Silvita; Prasetyo, Opik; Rachman, Hening Triandika (Universitas Syiah Kuala, 2024)
The lack of teacher information regarding the scientific knowledge contained in the process of making tempeh gembus has an impact on students' low analytical thinking skills. This study aims to: (1) analyze the scientific knowledge in the process of making tempeh gembus; (2) analyze the potential of scientific knowledge in the process of making tempeh gembus towards empowering students' analytical thinking skills; and (3) analyze the correlation of scientific knowledge in the process of making tempeh gembuswith the basic competencies in science learning materials. This research is a qualitative descriptive study with an ethnographic approach. The primary data sources for this research are from observations and interviews with tempeh gembus producers and junior high school science teachers in the Karangpandan District. The sampling technique used is snowball sampling. Data collection is carried out through observation, interviews, and documentation. The instrument validity test technique uses expert validation (two experts). Data validity test technique uses triangulation of data collection techniques. Data analysis is conducted using Miles and Huberman's interactive model analysis. The results show that the process of making tempeh gembus contains scientific knowledge (aspects of physics, chemistry, and biology). The scientific knowledge in the process of making tempeh gembus has the potential to empower students' analytical thinking skills. The scientific knowledge in the process of making tempeh gembus presented in booklet form is related to the basic competencies in junior high school science learning materials